2021
DOI: 10.1109/access.2021.3053054
|View full text |Cite
|
Sign up to set email alerts
|

Graph Regularized Hierarchical Diffusion Process With Relevance Feedback for Medical Image Retrieval

Abstract: Befitting from the interpretability and the capacity in capturing the underlying manifold structure, diffusion process (DP) has attracted increasing attention in the field of image retrieval. Within it, hierarchical diffusion process (HDP) has achieved satisfactory results in retrieved performance and complexity. However, the existing hierarchical diffusion process methods only diffuse the affinity values in low-level visual space without considering the high-level semantic information, which cause the problem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…Results of retrieval are used for retuning the model, and estimating the best hyperparameters for efficient model performance. Due to which, the proposed model is 18% more accurate than GRH [2], 36% more accurate than RaLM [5], and 34% more accurate than DHV [16], while it has 14% more recall than GRH [2], 19% more recall than RaLM [5], and 29% more recall than DHV [16] for different types of medical images. Similar observations were obtained for precision, fMeasure and AUC performance, which indicates that the model is useful for a wide variety of medical image retrieval applications.…”
Section: Conclusion and Future Scopementioning
confidence: 97%
See 4 more Smart Citations
“…Results of retrieval are used for retuning the model, and estimating the best hyperparameters for efficient model performance. Due to which, the proposed model is 18% more accurate than GRH [2], 36% more accurate than RaLM [5], and 34% more accurate than DHV [16], while it has 14% more recall than GRH [2], 19% more recall than RaLM [5], and 29% more recall than DHV [16] for different types of medical images. Similar observations were obtained for precision, fMeasure and AUC performance, which indicates that the model is useful for a wide variety of medical image retrieval applications.…”
Section: Conclusion and Future Scopementioning
confidence: 97%
“…This improvement in precision is due to use of application specific retrieval method selection, which makes the model highly useful for clinical applications. From the fMeasure evaluation, it is observed that the proposed model has 14% more fMeasure than GRH [2], 18% more fMeasure than RaLM [5], and 26% more fMeasure than DHV [16] for different types of medical images. This improvement in fMeasure is due to improvement in precision & recall performance.…”
Section: Design Of Performance Validation and Model Retuning Unit Usi...mentioning
confidence: 99%
See 3 more Smart Citations